An Evaluation of MSDC-0160, A Prototype mTOT Modulating Insulin Sensitizer, in Patients with Mild Alzheimer’s Disease - Shah, Raj C (Bentham Science Publishers, 2014)
Alzheimer’s disease (AD) is associated with insulin resistance and specific regional declines in cerebral metabolism. The effects of a novel mTOT modulating insulin sensitizer (MSDC-0160) were explored in non-diabetic patients with mild AD to determine whether treatment would impact glucose metabolism measured by FDG-PET in regions that decline in AD. MSDC-0160 (150 mg once daily; N=16) compared to placebo (N=13) for 12 weeks did not result in a significant difference in glucose metabolism in pre-defined regions when referenced to the pons or whole brain. However, glucose metabolism referenced to cerebellum was maintained in MSDC-0160 treated participants while it significantly declined for placebo patients in anterior and posterior cingulate, and parietal, lateral temporal, medial temporal cortices. Voxel-based analyses showed additional differences in FDG-PET related to MSDC-0160 treatment. These exploratory results suggest central effects of MSDC-0160 and provide a basis for further investigation of mTOT modulating insulin sensitizers in AD patients.